CHEMICAL STRUCTURE OF SUBSTANCES CONTAINED IN PEANUTS IN THE TREATMENT OF DIABETES DISEASE (Scientific journal of the Fergana State University, 2023)
Biologically active substances are used in medicine and in the prevention of diseases, as well as to ensure a high level of vital activity. This article provides information on the biologically active substances found in peanuts, their beneficial properties and chemical structure.